2010
DOI: 10.1038/nature09217
|View full text |Cite
|
Sign up to set email alerts
|

The prion protein as a receptor for amyloid-β

Abstract: Increased levels of brain amyloid-beta, a secreted peptide cleavage product of amyloid precursor protein (APP), is believed to be critical in the aetiology of Alzheimer's disease. Increased amyloid-beta can cause synaptic depression, reduce the number of spine protrusions (that is, sites of synaptic contacts) and block long-term synaptic potentiation (LTP), a form of synaptic plasticity; however, the receptor through which amyloid-beta produces these synaptic perturbations has remained elusive. Laurén et al. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
208
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(218 citation statements)
references
References 14 publications
8
208
0
1
Order By: Relevance
“…2 Even more recently, evidence of PrP C acting as an Aβ oligomer receptor has emerged. [3][4][5][6] Yet, the potential impact on physiologic processes associated with learning and memory such as long-term potentiation and synaptic plasticity have been discussed rather controversially. By acting as an Aβ oligomer receptor, initiation of cascades leading to neuronal on which selective interactions with many ligands and transmembrane signaling pathways translate into wide-range consequences upon both physiology and behavior."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Even more recently, evidence of PrP C acting as an Aβ oligomer receptor has emerged. [3][4][5][6] Yet, the potential impact on physiologic processes associated with learning and memory such as long-term potentiation and synaptic plasticity have been discussed rather controversially. By acting as an Aβ oligomer receptor, initiation of cascades leading to neuronal on which selective interactions with many ligands and transmembrane signaling pathways translate into wide-range consequences upon both physiology and behavior."…”
Section: Discussionmentioning
confidence: 99%
“…2 Especially PrP C 's role as a potential Aβ oligomer receptor and their conjoint impact on long-term potentiation (LTP), synaptic plasticity and neuronal death have been discussed controversially. [3][4][5][6] Although the overall expression of PrP C in the brain appears to be similar in healthy Background/Objective: PrP c has been suggested to play a role in aD pathophysiology. csF concentrations of PrP c have been shown to be reduced in aD compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Such assumptions do not apply to wild-type mice, which may comprise a PrP expression. 49,50 More recently, however, Freier et al reported that standardized Aβ-derived diffusible ligand (ADDL) preparations disrupt hippocampal synaptic plasticity in a PrP-dependent manner and that Aβ obtained from ex vivo human material does the same. Furthermore, using monoclonal antibodies directed at two different PrP C epitopes, these and other authors successfully blocked the Aβ-mediated disruption of synaptic plasticity.…”
Section: Proteolytic Pathwaysmentioning
confidence: 99%
“…14 In contrast, some studies indicate that PrP C is not required for Aβ oligomer-induced cognitive impairment since the PrP C expressing and knockout mice have no difference in Aβ oligomer-induced synaptic depression, spine density loss, and deficiency of long-term potentiation. 15 Two intracerebroventricular injections of Aβ oligomers to wild-type or PrP C null mice have suggested no PrP C effect on Aβ oligomer-induced memory dysfunction, 10 and modulation of PrP C in AD transgenic mouse models shows no effect on the impairment of the hippocampal synaptic plasticity. 16 Furthermore, PrP C deficiency does not ameliorate abnormal neural network activity or cognitive dysfunction in one type of AD model mice.…”
mentioning
confidence: 99%